Advantages of breastfeeding for the mother-infant dyad - Zuzanna Chęcińska-Maciejewska; Andrzej Ciborek; Hanna Krauss; Magdalena Gibas-Dorna (Journal of Health Inequalities)
Breastfeeding is considered to be the best and optimal mode of infant feeding, providing health benefits for both the child and the mother. Maternal milk contains all the necessary nutrients, strengthens the baby’s immune system, reduces the risk of cancer, allergies, and food intolerances, supports nervous system development, and provides emotional benefits for both baby and mother. The advantages of breastfeeding for mothers also include protection from lowered mood disorders, lowered risk of some types of cancer and cardio-metabolic disorders, and chronic inflammatory disorders. Modified milk feeding is available when breastfeeding is impossible or unwilling; however, it cannot offer as many vital nutritional and health benefits as human milk. Although breastfeeding is highly recommended by the World Health Organization and scientific associations as the best and optimal nutrition during the first months of life, some mothers still decide to choose infant formula as an acceptable and safe alternative. This is usually due to inadequate knowledge of breastfeeding benefits, poor family and professional support, or marketing of infant formula. In fact, infant formula is a good option but only when breastfeeding is unavailable. Therefore, it is important for mothers to make decisions about the type of feeding based on the actual state of knowledge regarding health benefits, medical counselling, individual needs, and other important circumstances. This paper provides an overview of the advantages of breastfeeding for infants and their mothers according to the current literature.